Lower-limb kinematic characteristics of taekwondo kicks at different attack angles - Liu, T.-T.; Lin, Y.-C.; Tang, W.-T.; Hamill, J.; Chang, J.-S. (International Journal of Performance Analysis in Sport, 2021)
The aim of the present study was to investigate the variation of lower-limb kinematic characteristics and movement patterns in elite taekwondo competitors when performing roundhouse kicks at various attack angles. Nineteen male elite athletes specialising in roundhouse kicks were asked to kick a target at 90°, 60°, and 30°. A three-dimensional (3D) motion capture system was used to collect kinematic data. Kinematic parameters were compared among the conditions using a one-way repeated measures analysis of variance (p < 0.05). The variables; peak linear velocity at the pelvis, maximum left-pelvis tilt, posterior pelvis tilt, left pelvis internal rotation angles, posterior pelvic tilt angular velocity, and left pelvis rotation velocity; were greater at the larger attack angles. Moreover, the maximum distal knee joint flexion was greater whereas the maximum flexion angle of the proximal hip joint was smaller at a larger attack angle. This study identified the kinematic differences in lower-limb motion between roundhouse kicks performed at different attack angles. Taekwondo athletes should adjust not only their rotational but also their linear kinematics at the more proximal segments and joints to cope with different attack angles.